1994
DOI: 10.2307/3578659
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extracellular and Intracellular pH on Repair of Potentially Lethal Damage, Chromosome Aberrations and DNA Double-Strand Breaks in Irradiated Plateau-Phase A549 Cells

Abstract: Plateau-phase A549 cells exhibit a high capacity for repair of potentially lethal radiation damage (PLD). Previously it was found that PLD repair could be partially inhibited by increasing the extracellular pH (pHe) of the spent medium from its normal value of 6.7-6.8 to 7.6 during postirradiation holding. The present study shows that PLD repair is also inhibited by reducing the pHe of the spent medium to 6.0. The effects of altering pHe on rejoining of DNA double-strand breaks (DSBs) as measured by neutral fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Radiocurability may depend upon a combination of sublethal and potential lethal damage repair [28] and both mechanisms may have a similar molecular basis [29]. The higher recovery ratio for A549 cells reported here falls within the range of 40 to 70 found for potential lethal damage repair [9,30].…”
Section: Repair Of Sublethal Damagesupporting
confidence: 59%
See 1 more Smart Citation
“…Radiocurability may depend upon a combination of sublethal and potential lethal damage repair [28] and both mechanisms may have a similar molecular basis [29]. The higher recovery ratio for A549 cells reported here falls within the range of 40 to 70 found for potential lethal damage repair [9,30].…”
Section: Repair Of Sublethal Damagesupporting
confidence: 59%
“…Recovery of sublethal damage as a function of time was obtained from: S(t) ‫ס‬ S 0 + (S max − S 0 )(1 − e −k.t ) [9], where S 0 is the surviving fraction at time t ‫ס‬ 0 and S max is the maximum surviving fraction reached in the split dose experiment and k is the repair rate. Halftimes for repair (T 1 /2 ) were calculated as follows [10]: T 1 /2 ‫ס‬ Ln2/k ‫ס‬ 0.693/k, where k is the repair rate as calculated above.…”
Section: Determination Of Sublethal Damage Repairmentioning
confidence: 99%
“…Cells exposed to hypoxia and low pH have been reported to exhibit a diminished capacity for DNA repair compared with control cells grown under standard culture conditions ( 52 ). Significant inhibition of rejoining double-stand DNA breaks (DSBs) also has been observed when irradiated cells are maintained at pH 6.0 ( 53 ). Although other effects, including the pH-dependence of polymerase enzymes ( 54 , 55 ) contribute to this behavior, pH-dependent interactions between XRCC1/4 and FHA domain proteins, including PNKP, APTX and APLF, may be an important contributor under some circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…clastogenicity [118]. The maintenance of such aberrations would be facilitated by the fact that a low pH e could also alter the DNA repair process [119,120]. Interestingly, data obtained by Massonneau and coworkers [121] have recently indicated that even rather small variations of pH e (from 7.2 to 6.9) could lead to impairment of the DNA repair; as a result, the genotoxicity of double-stranded breaks would be enhanced, leading to genetic instability.…”
Section: -4-1-extracellular Acidosis and Dna Repairmentioning
confidence: 99%